Effect of Flow Rate on Adsorption Cadmium Ion (II) Using Activated Carbon of Langsat Shell (Lansium Domesticum Corr) - Farras Shafa Nabila; Desy Kurniawati (Indonesian Journal of Chemical Science and Technology (IJCST), 2023)
Cadmium is one of the dangerous heavy metals contained in industrial wastewater whose presence needs to be addressed. Adsorption is one method that can be used to reduce the levels of heavy metal ions contained in wastewater. Langsat peel activated carbon is used as an adsorbent to adsorb cadmium metal because it is easy to obtain and its use is still minimal in the community. The langsat peel was made into activated carbon with HNO3 activator as a metal ion absorber Cd2+ using the column method. The activated carbon obtained has been tested for quality according to the Indonesian National Standard (SNI) No.06-3730-1995. In this study, we determined the effect of flow rate on metal cadmium absorption. The results showed that the activated carbon met the quality standards set by SNI and the optimum value of Cd2+ metal ion adsorption was at a flow rate of 1 ml/min.